AUTOMATED PHOTOPLETHYSMOGRAPH - V. A. Alekseev; S. A. Ardashev; S. I. Yuran (Приборы и методы измерений)
Automated photoplethysmograph for registration the pulse curves, technical characteristics of the device and results of its experimental approbation are presented. Developed photoplethysmograph is expedient to use for research purposes on perfection of designs of optoelectronic sensors for specific bioobjects and sites of biofabrics. That will allow raising the level of diagnostics of cardiovascular system condition of people and animals.